2018
DOI: 10.1007/s13595-018-0784-9
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of climate effects on the height-diameter relationships of tree species

Abstract: Key message The mean temperature from March to September affects the height-diameter relationship of many tree species in France. For most of these species, the temperature effect is nonlinear, which makes the identification of an optimal temperature possible. Increases in mean temperature could impact the volume supply of commercial species by the end of the twenty-first century.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(31 citation statements)
references
References 42 publications
5
26
0
Order By: Relevance
“…For the sake of generality, ForCEEPS relies on generic DBH–height relationships, although these relationships are known to change with tree age and tree density (Fortin et al., 2019; Trouvé et al., 2015). Improvements in this direction may be possible, even though calibrating this allometric parameter would require more detailed inventory data (Rasche et al., 2012), and may have a very limited effect on the model's results when compared to the effect of other parameters (see sensitivity analysis of the ForCLIM model by Huber et al., 2018 and Morin et al., 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the sake of generality, ForCEEPS relies on generic DBH–height relationships, although these relationships are known to change with tree age and tree density (Fortin et al., 2019; Trouvé et al., 2015). Improvements in this direction may be possible, even though calibrating this allometric parameter would require more detailed inventory data (Rasche et al., 2012), and may have a very limited effect on the model's results when compared to the effect of other parameters (see sensitivity analysis of the ForCLIM model by Huber et al., 2018 and Morin et al., 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The whole NFI dataset was used for the parameterization to cover the largest range of conditions in which each species occurs. Although diameter–height relationships were shown to be affected by environmental conditions, for example, climate, tree social status and stand density (Fortin et al., 2019; Trouvé et al., 2015), these factors were not accounted for in the model. The rationale for this lies in our aim to keep the model structure as simple as possible to allow for an easy parameterization and use at large scale for a large number of species.…”
Section: Parameterization Validation and Sensitivity Analysismentioning
confidence: 99%
“…Therefore, the application of these models is restricted to the range of data as well as to the Northern Iberian Range, because species-mixing effects can vary among regions [33,34]. Climate-sensitive models could have broader applications for h-d relationships and tree growth functions [77,78]; however, analyzing climatic effects is beyond the scope of this study, both because of the narrow geographical amplitude of the triplet network and the relatively short growth series. However, further work is needed to test if the specific years and annual fluctuations in climatic variables might affect the basal area growth and the h-d relationships, or shift the effect of species-mixing on productivity and tree allometry.…”
Section: Implication For Tree-level Model In Mixed Standsmentioning
confidence: 99%
“…The responses of trunk and leaf traits to the climate variability have been well studied (Fortin et al, ; Iida et al, ; Niinemets, ; Ordoñez et al, ; Tingstad et al, ; Wright et al, ). For example, it was found that taller trees incline to occur at places with higher water availability (Tao et al, ) and show higher vulnerability to droughts (Bennett et al, ), while at a given latitude of temperate biomes, larger and thinner leaves are easier to be found in a wetter environment (Lusk et al, ; Wright et al, ).…”
Section: Introductionmentioning
confidence: 99%